2014
DOI: 10.1007/bf03356521
|View full text |Cite
|
Sign up to set email alerts
|

Screening for broad mite susceptibility in Rhododendron simsii hybrids

Abstract: Broad mite Polyphagotarsonemus latus, is a key pest of pot azalea (Rhododendron simsii Planch hybrids). No information on variation in susceptibility or potential tolerance within these plants is available to date. We evaluated a selection of 32 Rhododendron cultivars, mainly R. simsii hybrids, for susceptibility to broad mite. The plants were artificially infested in a greenhouse by surrounding each azalea with four broad mite-infested English ivy plants (Hedera helix). Broad mite infestation was evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…A small number of 20 mites or less can cause serious economic damage in crops such as pepper [8,9], cucumber [10], lime [9] and chili [9,11]. Also in pot azalea, it has been shown that low mite numbers can lead to high damage rates [12]. Even after treatment, symptoms may continue to develop [13] and damage initiated in a plant progresses even when mites are no longer present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of 20 mites or less can cause serious economic damage in crops such as pepper [8,9], cucumber [10], lime [9] and chili [9,11]. Also in pot azalea, it has been shown that low mite numbers can lead to high damage rates [12]. Even after treatment, symptoms may continue to develop [13] and damage initiated in a plant progresses even when mites are no longer present.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in susceptibility to broad mites have been observed in pot azalea, along with the damage rate, and in relation to the population sizes of P. latus on the tested azalea cultivars [12]. Trichomes (plant hairs) are potentially involved in broad mite resistance in pot azalea [14].…”
Section: Introductionmentioning
confidence: 99%
“…Plant resistance to P. latus has been found in several plant species (Luypaert et al, 2014). The presence and density of trichomes have been reported as a predominant factor related to plant resistance/defence to this mite (Thungrabeab & Boonlertnirun, 2002;Matos et al, 2009;Luypaert et al, 2014). This constitutive physical trait, though, is not the only defence mechanism identified until now.…”
Section: Introductionmentioning
confidence: 99%
“…As an important ornamental pot plant in China, western Europe, USA, and Japan, R. simsii was introduced to Europe from Asia at the end of the 18th century (Galle 1985). Wild R. simsii germplasm resources are still today used to develop new cultivars with desired ornamental characters (Luypaert et al 2014). Furthermore, R. simsii plays a vital roles in preventing soil erosion and maintaining stability of forest ecological systems (Hahn et al 2017).…”
Section: Introductionmentioning
confidence: 99%